EKSPERIMENTASI MODEL PEMBELAJARAN TWO STAY TWO STRAY (TSTS) DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SAINTIFIK PADA MATERI HIMPUNAN DITINJAU DARI KECERDASAN LOGIS-MATEMATIS - Andhika, Niken Dwi; Usodo, Budi; Subanti, Sri (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from studentâs logical-mathematical intelligence. The learning model compared were classical with scientific approach, TSTS with scientific approach, and TPS with scientific approach. This was quasi-experimental research with 3x3 factorial design. The population were all students of Junior High School in Pati. The samples are the students of SMPN 3 Pati, SMPN 8 Pati, and SMPN 2 Margorejo, which taken by using stratified cluster random sampling technique. The instruments used were mathematics achievement test and matematical-logical intelligence test. The data analysis technique was used unbalanced two ways anova. Based on the data analysis, it can be concluded as follows. (1) TSTS with scientific approach gives better mathematics achievement than TPS with scientific approach, and both gives better mathematics achievement than classical with scientific approach. (2) Mathematics achievement of students who have high logical-mathematical intelligence was better than students who have medium logical-mathematical intelligence, and both gives better mathematics achievement than students who have low logical-mathematical intelligence. (3) For classical with scientific approach, mathematics achievement of students who have high logical-mathematical intelligence was better than students who have medium logical-mathematical intelligence, and both gives better mathematics achievement than students who have low logical-mathematical intelligence. For TSTS with scientific approach and TPS with scientific approach, students who have high and medium logical-mathematical intelligence have the same mathematics achievement, and both have the better mathematics achievement than low logical-mathematical intelligence. (4) For students who have high and low logical-mathematical intelligence, all learning models gives the same mathematics achievement. For students who have medium logical-mathematical intelligence, TSTS with scientific approach gives the better mathematics achievement than classical with scientific approach. TSTS with scientific approach and TPS with scientific approach gives same mathematics achievement. TPS with scientific approach and classical with scientific approach gives the same mathematics achievement.Keywords: Classical, Two Stay Two Stray (TSTS), Think Pair Share (TPS), Scientific Approach, logical-mathematical intelligence